Dynamics Analysis and Intermittent Energy Feedback Control of m-HR Neuron Model under Electromagnetic Induction - Jiankui Peng; Suoping Li (Complexity)
It is of great practical significance to fully reveal the global discharge characteristics of neurons in electromagnetic environment and design effective energy feedback strategy for accurate prediction of neural information. Considering the effect of electromagnetic induction, a four-dimensional modified Hindmarsh–Rose (m-HR) neuron model is established, and its discharge mechanism is revealed by analyzing the existence and stability of equilibrium point of the model. Extensive numerical results confirm that the model has classical period-doubling bifurcation, period-adding bifurcation, and comb-shaped chaotic structure. Importantly, a new intermittent energy feedback controller is designed by improving the traditional energy feedback control strategy, which can effectively modulate the desired discharge modes under the cost-optimal energy consumption. Meanwhile, it should be emphasized that the intermittent control scheme has a wider range of regulation and robustness, which can be applied to other dynamical systems to obtain the desired oscillation modes. This will improve the beneficial discussion for the construction of brain-like intelligent network and efficient regulation.